PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA JUDI TOGEL BERDASARKAN KITAB UNDANG-UNDANG HUKUM PIDANA DI WILAYAH HUKUM KEPOLISIAN RESORT KOTA PEKANBARU - Hotman Maringin; Dodi Haryono; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Gambling is a form of the disease among the community and quite unsettling society, one form of gambling that are currently still thrives in the city of pekanbaru is crime gambling pools or sie jie, this gambling problem has long been that failed after. This society that the disease still thrives in the city of Pekanbaru, law enforcement officers have been trying to resort everything possible to eradicate the crime of gambling is but there are still selling these pools, let alone current with supported by an increasingly sophisticated technology where the coupon purchase pools or sie jie can use mobile or through short massage service (sms) so this is what makes the law enforcement apparatus Polresta city of Pekanbaru difficulty to catch bookies pools,in law enforcement against criminal acts of gambling pools there are barriers faced by investigator resort city of Pekanbaru lack of awareness of the law and the openness of society, so that they are only potentially dumb and silent,considered gambling it is something that is natural and only a small infraction, rapid science and technology also makes gambling is increasingly sophisticated, network of lotteries is closed, efforts are being made to overcome those barriers, law enforcement agencies have made efforts to prevention and mitigation, i.e. doing outreach to the community, law formed a special team to spy on a frequent place for pools (informants), patrol and surveillance on the community, doing research and investigation as well as an ambush against the practices of gambling pools.Keyword: law enforcement, community disease, gambling